TACTICS OF THE PATIENT MANAGEMENT IN THORACIC AORTA DILATION: SELECTION THE ASSESSMENT METHOD, RESULTS EVALUATION - E. B. Luneva; E. G. Malev; A. S. Rudoy; E. V. Zemtsovsky (Российский кардиологический журнал, 2015)
The article focuses on the review of the main methods of aorta visualization. The methods are described, as the algorithm of investigation method selection, strategy of patient’s management with aorta dilation. Special attention is paid for the patients with genetic disorders that may cause aorta dilation.